Thermokarst lake changes over the past 40 years in the Qinghai–Tibet Plateau, China - Li, Lan; Zhang, Xindi; Li, Xuan; Zhao, Shufang; Ni, Wankui; Yang, Zhenzhen (Frontiers in Environmental Science, 2022)
Thermokarst lake is defined as a lake that generally occupies closed basin caused by melting of massive ground ice in the ice-rich permafrost regions, which has a greater impact on the regional hydro-ecological equilibrium and permafrost engineering infrastructure facilities. Global warming and increasing human activities are accompanied by the permafrost degradation and glaciers retreat in the Qinghai-Tibet Plateau (QTP).The QTP, source of many international rivers in Asia, is known as the “Asian Water Tower”. As we know, the number and area of the lakes in the QTP increased in the past 40 years, however, the lakes area less than 1 km2 have been neglected when calculating the water storage. To address the evolution of thermokarst lakes in the QTP, the Modified Normalized Difference Water Index (MNDWI) and visual interpretation were applied to extract the water area based on Landsat data during 1980s to 2020. The result indicates that the thermokarst lake area reduced from 932.5 km2 to 799.25 km2 in the period of 1980s-1990, and from 1990 to 2020, the number and area of lakes kept sustainable grown, the number increased from 66506 to 120374, and the area increased by 113.14%. As a heat carrier, thermokarst lakes transfer heat vertically and horizontally. The temperature of surrounding permafrost rises as the increase of number and area of lakesand the permafrost has been extensively degraded. Also, long-time carbon stocks release into atmosphere in the process of lake formation, which affects the regional carbon cycle.